Carrying Capacity of Agricultural Land in Mojolaban Subdistrict, Sukoharjo – Central Java - Rohsulina, Pranichayudha; Rahman, MS Khabibur; Hidayat, Agung (Universitas Veteran Bangun Nusantara, 2020)
Analysis of the carrying capacity of agricultural land is one of the evaluation tools for sustainable development that can provide an overview of the relationship among population, agricultural land and the environment. This research aims to analyse the carrying capacity of agricultural land in each village in Mojolaban Subdistrict. Analysis of the carrying capacity of land in this research uses a concept developed by Sumarwoto (1985) where the magnitude of the carrying capacity of agricultural land is inversely proportional to population pressure. The results show that the carrying capacity of agricultural land in Mojolaban Subdistrict is inversely proportional to the population compressive pressure on agricultural land. Generally, the carrying capacity for agricultural land in Mojolaban Subdistrict is low level. There are 11 villages (73%) which have low carrying capacity for agricultural land and only 4 villages (27%) which have high carrying capacity of agricultural land.